P11 Mechanisms of ankle syndesmosis ligament injuries in male professional rugby union: a systematic video analysis of 8 cases. (17th September 2017) - Delahunt, E; Farrell, G; Kerin, F; Tierney, P
Abstract : Study Design: Case series. Objectives: To describe ankle syndesmosis ligament injury mechanisms in male professional rugby union players using systematic video analysis. Background: Current knowledge on ankle syndesmosis ligament injury mechanisms in male professional rugby union players is limited. Methods and Measures: We assessed videos from 8 ankle syndesmosis ligament injuries (confirmed via MRI) recorded via prospective injury surveillance in a professional rugby union club between 2013 and 2017. Three Chartered Physiotherapists independently reviewed all videos to determine specific playing situations and mechanisms leading to injuries. The playing situation at the time of injury was based on the classification used in the World Rugby injury surveillance studies. In a consensus meeting the three Chartered Physiotherapists agreed upon a descriptive analysis of the mechanism leading to injury. Results: Six of the cases analysed occurred during matches with the other two injuries sustained during training. Seven of the injuries were sustained during attacking situations. Of these, four were the result of the ball carrier being tackled by an opponent, one occurred during a maul, one during a ruck and one as a result of a collision with a teammate. The characteristic injury mechanisms included forced dorsiflexion with a fixed externally rotated foot, which were often compounded by an externally applied lateral force causing medial collapse of the knee and ipsilateral trunk flexion. Conclusions: In 7 of the 8 cases, ankle syndesmosis ligament injuries were sustained during attacking playing situations. Fifty per cent (n=4) of the injuries were the result of a player being tackled. The characteristic injury mechanism in all instances was an externally rotated foot position.